Helicobacter hepaticus Induce Colitis in Male IL-10−/− Mice Dependent by Cytolethal Distending Toxin B and via the Activation of Jak/Stat Signaling Pathway - Zhu, Liqi; Zhu, Chen; Cao, Shuyang; Zhang, Quan (Frontiers in Cellular and Infection Microbiology, 2021)
It has been well documented that cytolethal distending toxin (CDT) from Helicobacter hepaticus (H.hepaticus), Campylobacter jejuni (C.jejuni) and other gram-negative intestinal pathogens is linked to the inflammatory bowel disease (IBD). However, the mechanisms underlying the progression of H.hepaticus induced colitis remains unclear. In this study, male B6.129P2-IL10tm1Cgn/J mice were infected by H.hepaticus and ΔCdtB H.hepaticus for 6, 12, 18 and 24 weeks. Histopathology, H.hepaticus colonization levels, expression of inflammatory cytokines, signaling pathways and content of NO in proximal colon were examined. We found that Cytolethal distending toxin subunit B (CdtB) deletion had no influence on colonization ability of H.hepaticus in colon of B6.129P2-IL10tm1cgn /J mice, and there was no significant difference in abundance of colonic H.hepaticus over infection duration. H.hepaticus aggravated rectocele and proximal colonic inflammation, especially at 24 WPI, while ΔCdtB H.hepaticus could not cause significant symptom. Furthermore, mRNA levels of Il-6, Tnf-α, Il-1β and iNOS significantly increased in the proximal colon of H.hepaticus-infected mice compared to ΔCdtB H.hepaticus infected group from 12 WPI to 24 WPI. In addition, the elevated content of NO and activated Stat3 and Jak2 in colon were observed in H.hepaticus infected mice. These data demonstrated that CdtB promote colitis development in male B6.129P2-IL10tm1Cgn/J mice by induction of inflammatory response and activation of Jak-Stat signaling pathway.